Styryllactones from antidengue active fraction of a Goniothalamus lanceolatus leaves through in silico and in vitro evaluation / Nor Nadirah Abdullah - Abdullah, Nor Nadirah (2024)
Goniothalamus lanceolatus Miq. is an indigenous plant found in the rainforest of Sarawak. This ethnomedicinal plant has historically been used by native people as a mosquito repellent, to treat fevers, cancer, and abortion. The dichloromethane extract of leaves of G. lanceolatus (GLLD) showed promising results against DENV-2 with an IC50 value of 4.16 µg/mL, CC50 value of 24.23 µg/mL and a selectivity index (SI) of 5.82. This extract was selected for further fractionation to afford six fractions (F1-F6). These fractions were evaluated against DENV-2 (NGC strain) replication through plaque reduction assay. Based on the results, fraction F2 was identified as the most promising fraction against DENV-2 with an IC50 value of 1.62 µg/mL, CC50 value of 98.99 µg/mL, and a SI value of 61.10. Deep metabolome analysis of molecular networking highlighted that fraction F2 is mainly comprised of styryllactones and an itional 18 styryllactones were further annotated. Isolation and purification from this active anti-dengue fraction led to the characterization of eight styryllactones. All the structures were elucidated using 1D-NMR and 2D-NMR spectroscopy, whilst electronic circular dichroism data (ECD), NOESY experiments, and data comparison with literature values were used to establish the absolute configurations. The compounds were isolated during a bioactivity-directed comprising of two 2Htetrahydropyran derivatives, (one new 3-epi-goniothalesdiol A 1 and known goniothalesdiol A 2), one styryl-pyrone (goniodiol 3), three pyrano-pyrone (1S,5S,7R,8S-3-exo,7-endo-(+)-8-epi-9-deoxygoniopypyrone 4, deoxygoniopypyrone B 5, and parvistone D 6), one furano-pyrone ((+)-goniofupyrone B 7), and one bisstyryllactone (6S,7S,8S,6Sꞌ,7Sꞌ,8Sꞌ-(+)-goniolanceolatin A 8). The new compound 1 differs from the previously reported goniothalesdiol A in the absolute stereochemistry at position C-3 which was proposed as (2R,3R,4S,6R) and was named as 3-epigoniothalesdiol A. Interestingly, C-4 from pyrano moiety of 1 originated from C-6 of rare S-goniothalamin reported from G. lanceolatus. In vitro evaluation showed that compound 8 had a promising anti-dengue viral activity with the highest SI value of 4.06 and by qRT-PCR with an SI value of 5.30. The findings from in silico studies suggest that compound 8 has the potential to act as an inhibitor against the Envelope (E), NS5 methyltransferase, and NS5 RdRp proteins of DENV